Howard Gardner's Multiple Intelligences from the Perspective of Islamic Education - Yayah Badriyah; M. Djaswidi Al-Hamdani; Soni Samsu Rizal; Nurjanah Nurjanah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Education that humanizes humans is education that is able to educate and develop a person's personality covering all aspects. However, unfortunately intelligence is still often understood as an ability that is emphasized on certain aspects only. Thus, a broader and comprehensive concept of intelligence is needed. This study aims to determine the concept of multiple intelligences according to Howard Gardner and its relevance to the concept of Islamic education. This research is a qualitative research with literature study research method. The primary data of this research is sourced from Howard Gardner's book, Multiple Intelligences: Multiple Intelligences in Theory in Practice translated. Lyndon Saputra and secondary data sourced from books, journals and other literature related to the theory of multiple intelligences and Islamic education. Data collection is done by documentation technique. The data analysis technique uses content analysis. The results show that: 1) Multiple intelligences according to Howard Gardner are the ability to solve problems and create something that has cultural values, consisting of linguistic, logical-mathematical, spatial, musical, kinesthetic, interpersonal, intrapersonal, naturalist and existential intelligences. 2) Multiple intelligences in the perspective of Islamic education are interpreted that every human being has a nature since he was born, including: religious nature, reason, morality and character, cleanliness and purity, truth, independence, justice, equality and unity, social, individual, sexual, economics, politics and the arts. 3) The relevance of the concept of multiple intelligences according to Howard Gardner with the concept of Islamic education, namely, both of them explain that every human being has basic potential, is equally oriented to the development of potential, recognizes various kinds of intelligence and there are several verses of the Qur'an which contain an explanation of each. -each intelligence in Howard Gardner's multiple intelligences.